الأحكام الفقهية المأخوذة من حديث : (( ثلاث ساعات كان رسول الله ( صلَّى الله عليهِ وسلَّم ) ينهانا أَن نصلِّي فيهنَّ)). - Mohammed Mahmood Saleh Ahmed (Islamic Sciences Journal, 2026)
Our Merciful Prophet, the Merciful One, our Master Muhammad (peace and blessings be upon him), upon him be the best of prayers and the most complete of peace, forbade us from praying at three times and hours, and also from burying our dead during them. The explanation and rationale for this prohibition are found in a Hadith of our noble Prophet in Sahih Muslim. In general, our true religion does not command anything or forbid anything unless its purpose is to serve the public interest and for a reason that he knows, I have explained the hadith and the statements of eminent scholars regarding this prohibition. And God Almighty is the One who grants success and assistance.